Answer:
In the two different ways we have solved the given equation as
![x=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ywjf3c19bhavgfxc769seziwm0bus63jxi.png)
Explanation:
Given expression is
![(2)/(3)(3x+6)=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xpx5ri5rbdd0qyrw66pf64c43anod57ggq.png)
To simplify the given expression in two ways:
First way:
Given
![(2)/(3)(3x+6)=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xpx5ri5rbdd0qyrw66pf64c43anod57ggq.png)
![(2)/(3)(3x+6)=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xpx5ri5rbdd0qyrw66pf64c43anod57ggq.png)
![(6x+12)/(3)=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/f9ev7kpzrorv4uadvldrahvqy8yndwvqwl.png)
Multiplying 3 on both sides
![3* ((6x+12)/(3))=3* (4x+3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/65k3if4uh2otkms3fg2hwn50n5gy08ny8z.png)
![6x+12=12x+9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8xvwalsahljl0x9q2g0p1yqbwoc283kvkk.png)
(adding the like terms)
![-6x+3=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y9lrq6358vnhagc2jrgdlehi0uo151871s.png)
![3(-2x+1)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1hckiueai1r76hskdorvk3yeltutd148z0.png)
Dividing by 3 on both sides
![3(-2x+1)* \frac{1}3}=0* \frac{1}3}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j1eojnoau7gfwgej8wfqyg7q3e22t0lz37.png)
![(-2x+1)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/983up0jc571oec3361w6gvyah70bzywzba.png)
![-(2x-1)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/drnrnh7sp68vr9ijfpwefx151961dqdwvf.png)
![2x-1=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tpo3t15cgdxmx7aecb5h579kwbz1w92w5s.png)
![x=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ywjf3c19bhavgfxc769seziwm0bus63jxi.png)
Therefore the given expression is solved that
![x=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ywjf3c19bhavgfxc769seziwm0bus63jxi.png)
Another way:
Given
![(2)/(3)(3x+6)=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xpx5ri5rbdd0qyrw66pf64c43anod57ggq.png)
![(2)/(3)(3x+6)=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xpx5ri5rbdd0qyrw66pf64c43anod57ggq.png)
![2((3x)/(3)+(6)/(3))=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tr6g1o7z9hrsn824djutzu57ylbrtrmor2.png)
![2(x+2)=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y9uq22aupb4srfekwh5b38uuobpbsd07ju.png)
![2x+4=4x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/87plqxn4bg6dunn4gchmjv5rt3xf5yesxw.png)
(adding the like terms)
![2x-1=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tpo3t15cgdxmx7aecb5h579kwbz1w92w5s.png)
![x=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ywjf3c19bhavgfxc769seziwm0bus63jxi.png)
Therefore the given expression is solved that
![x=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ywjf3c19bhavgfxc769seziwm0bus63jxi.png)
In the two different ways we have solved the given equation as
![x=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ywjf3c19bhavgfxc769seziwm0bus63jxi.png)